Evaluation of PT XYZ'S Strategy Through External and Internal Environmental Analysis using the Swot Approach - Helga, Aisyah Elvina; Joumil Aidil Saifuddin Z.S (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research aims to analyze and evaluate PT XYZ's corporate strategy so that it can determine the company's strategic position and can increase competitiveness, achieve maximum profitability and ensure business sustainability. The methods used are qualitative and quantitative approaches. The data collection technique in this study is direct interviews with employees at PT. XYZ, the questionnaire was distributed to the Company's Top Management. and systematically observing the phenomena that exist in the company. The data analysis technique used is a SWOT analysis which analyzes the company's external environment using PESTEL analysis and Porter's Five Forces to analyze the Company's internal environment using the value chain. The results of the study show that the PESTEL analysis provides a broader picture of more macro external factors that can affect the company's performance. Porter's Five Forces can identify areas that require attention in formulating strategies to improve competitiveness and profitability in a dynamic market. From the results of the SWOT analysis and the calculation of the Internal Matrix External Factors Evaluation (EFE) and Factors Evaluation (IFE) matrix, the total EFE matrix score is 2.96 and the total IFE matrix score is 3.14 so that the Company's position is in quadrant IV, namely grow and build. Alternative strategies used are market penetration, product development, and market development.